Hydrothermal deposition as a novel method for the preparation of Co-Mn mixed oxide catalysts supported on stainless steel meshes: application to VOC oxidation - Topka, Pavel; Jirátová, Květuše; Dvořáková, Michaela; Balabánová, Jana; Koštejn, Martin; Kovanda, František (Environmental science and pollution research international, 2022)
The aim of this work was to develop a novel method for the preparation of structured Co-Mn mixed oxide catalysts: deposition on stainless steel meshes by hydrothermal synthesis. The use of meshes enabled the deposition of a thin layer of the active phase, which significantly suppressed the influence of internal diffusion. Consequently, the prepared catalysts exhibited from 48 to 114 times higher catalytic activity in ethanol oxidation than the commercial pelleted Co-Mn-Al catalyst. Moreover, we have shown that their catalytic activity correlated with the proportion of surface oxygen vacancies determined by XPS. Finally, the outstanding activity of the catalyst with Co:Mn ratio of 0.5 was ascribed to the mutual effect of high number of oxygen vacancies and exceptional redox properties.
Keywords: Ethanol total oxidation; Cobalt–manganese mixed oxides; Structured catalysts; Hydrothermal reaction; katalýza; oxidace-redukce; těkavé organické sloučeniny; Catalysis; oxidy; Volatile organic compounds; Stainless steel meshes; Oxidation-Reduction; Stainless Steel; nerezavějící ocel; Oxides; Volatile Organic Compounds